Implementasi Pancasila di Era Digital : Tantangan dan Peluang Generasi Z - Naziha Afsi; Faras Nurfadillah; Hana Nafisah; Muhammad Lazuardy; Herli Antoni (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The values contained in Pancasila have always been fixed, which has shifted only to individuals who practice the principles of Pancasila has begun to fade due to the evolution of the times. Generation Z witnessed the loss of Pancasila values, nationalism and patriotism in them because they were too affected by the advancement of science and technology, the wave of globalization, and unlimited interaction. For this reason, it is necessary to apply Pancasila to change this behavior. In this study, qualitative analysis or approach is applied, namely research methods whose theories or discussions are obtained from various sources such as books, journals, articles, and others. emphasizing the observation of phenomena and deepening the substance of the meaning of the phenomenon. This study was carried out to increase the spirit of nationalism so that this generation does not care about the values contained in Pancasila. Therefore, the values contained in Pancasila must always be applied in daily activities.